Digital literacy readiness: Voices of indonesian primary and secondary english teachers - Bambang Widi, Pratolo; Nur, Fatimah; Soviyah, .; Zuraina, Ali (Universitas Ahmad Dahlan, 2022)
The ways students learn nowadays have changed significantly since the Covid 19 pandemic in 2019. Students today need different ways of teaching as they also have different learning styles. This study is intended to investigate how much the Indonesian primary and secondary English teachers are technologically literate, identify the challenges they face in teaching using technology and describe their hopes and expectation in their professional work as English teachers. Questionnaires in the form of google form were used to collect the data from all the participants, while interview was used to collect the data from the selected participants. The findings showed that most of the participants possessed high level of digital literacy, suggesting that they had the skills needed to help them teach online classes using the available online teaching platforms. They seemed to enjoy teaching online classes as they were capable of exploiting the online resources as the teaching materials, developing the available resources and even creating the digital teaching materials and using it in their online classes. The most serious problem they had was lack of IT knowledge in regard with the new online teaching platforms and internet connection. If they had to use the new online teaching platform, they had to learn it on their own, usually through YouTube and teach how to use it to their students. The classic problem, the internet connection, still occurred among the teachers and it caused problems in delivering the teaching materials and assessing the students’ work. This implies that the policy makers need to design professional development program which would help the Indonesia English teachers cope with their technological issues.